Analysis of the impact of the new Athens airport on urban air quality with contemporary air pollution models. (4th August 2014) - Moussiopoulos, N.; Sahm, P.; Karatzas, K.; Papalexiou, S.; Karagiannidis, A.
The new airport of Athens will be constructed in the Spata area to the east of the Athens basin. In an attempt to reveal how the airport operation will influence air quality in Athens, the transport of air pollutants in the Athens basin and the Spata area is studied by applying a set of contemporary models, all constituents of the European Zooming Model (EZM). Simulations were performed for meteorological conditions favouring the occurrence of air pollution episodes. Emphasis is put on the influence of the airport emissions on air quality, assuming that the airport is operating either at its old location (Hellenikon) or at Spata. All models agree well that, under conditions favouring air mass penetration from Athens to the Spata area, the resulting pollutant transport causes an increase in air pollution levels without, however, leading to the exceedance of air quality standards. In the opposite case, the transport of pollutants cannot have a noticeable adverse influence on the Athens air quality because of both the relatively high urban air pollution levels and the small penetration depth.